Canada orientale nell' America settentrionale - Coronelli, Vincenzo, 1650-1718 ([Venice], 1688)
Hand coloured. Depths shown by soundings. Decorative title cartouche. Compass rose. Includes notes. Five bar scales in decortative cartouche: Italian miles, French leagues, Spanish leagues, German leagues, and common sea leagues. "Dedicata Alli Mts. Reverendi Padri Li P.P. Minori Conuentuali del Monastero in signe di S. Francesco di Bologna" (dedication in title cartouche).